Pengetahuan, Perilaku Masyarakat Tentang Sanitasi Dasar Dan Kejadian Diare Di Puskesmas Sebatung Kabupaten Kotabaru - Khairina Latifah; Abdul Khair; Noraida Noraida; Juanda Juanda (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
The prevalence rate of diarrhea in Kotabaru Regency is 8.57%, which is the second highest number of cases after Hulu Sungai Utara. Data on diarrhea cases from the Kotabaru District Health Office stated that the Puskesmas with the highest number was the Sebatung Health Center. The purpose of this study was to determine the relationship between the knowledge and behavior of the community about basic sanitation and the incidence of diarrhea in the working area of ​​the Sebatung Health Center, Kotabaru Regency. The study analysis design used a case-control study method with a 1:2 case-control comparison. Data analysis using the chi-square test. The results showed that the level of community knowledge was 70% in the good category and 30% in the poor category, and the behavior of the community was 70% in the good category and 30% in the bad category. The results of statistical tests showed that knowledge (p value 0.000 < 0.05) was associated with the incidence of diarrhea, and behavior (p value 0.000 < 0.05) was associated with the incidence of diarrhea. It is hoped that it will increase knowledge and behavior about basic sanitation.